Alpha dogs the Americans who turned political spin into a global business - Harding, James 1969- (New York Farrar, Straus, and Giroux, 2008)
This is the story of two men who served as backroom strategists on every presidential contest from Richard Nixon to George W. Bush. David Sawyer was a New England aristocrat with dreams of becoming a filmmaker; Scott Miller, the son of an Ohio shoe salesman, had a knack for copywriting. Unlikely partners, they became a political powerhouse, directing democratic revolutions from the Philippines to Chile, steering a dozen presidents and prime ministers into office, and instilling the campaign ethic in corporate giants from Coca-Cola to Apple. The men of Sawyer-Miller were a small but extraordinary group who invented an American style of political campaigning and exported it around the world. Theirs is a story full of office intrigue, fierce rivalries, and disastrous miscalculations. And it is the tale of how world politics became American, and how American business became political.--From publisher description
Includes bibliographical references (p. 233-234) and index
1
Keywords: Sawyer Miller (Firm) -- Biography; Sawyer Miller (Firm) -- History; Campaign management -- United States -- History -- 20th century; Globalization -- Case studies; Media consultants -- United States -- Biography; Media consultants -- United States -- History -- 20th century; Political campaigns -- United States -- History -- 20th century; Political consultants -- United States -- Biography; Political consultants -- United States -- History -- 20th century; Public relations and politics -- United States -- History -- 20th century